Pola Perkembangan Tematik Teks Hortatori Eksposisi untuk Siswa Kelas Dua Belas - Siska Anggita Situmeang; Sanggam Siahaan; Basar Lolo Siahaan (CV. AFDIFAL MAJU BERKAH, 2026)
The English curriculum aim for F phase students in Indonesia develops the critical thinking skill on the production and comprehension of coherent texts in a social context. This research is to explore the thematic progression of a hortatory exposition for twelfth grade students. This research applied a qualitative research method. The results show 7 or 43.75% constant theme pattern, 6 or 37.50% zigzag theme pattern, 3 or 18.75% new brand theme pattern, 15 or 93.75% constant rheme pattern, and 1 or 6.25% evaluation rheme pattern in the text. The results also show 11 or 64.70% unmarked topical theme, 1 or 5.88% marked topical theme, and 5 or 29.41% textual themes. The results also show 10 or 58.82% noun phrases, 1 or 5.88% conjunction phrase + adverbial phrase + sentence subject, 3 or 17.64 conjunctions + sentence subjects, 2 or 11.76% prepositional phrases + sentence subjects, and 1 or 5.88 clauses. English textbook writers, teachers, and 12th grade students need to apply noun phrase, adverbs, conjunction, and preposition plus sentence subject to realize topical and textual themes in constant and zigzag thematic progression pattern in the production and interpretation of a coherent hortatory exposition text.